2019
DOI: 10.1097/tp.0000000000002429
|View full text |Cite
|
Sign up to set email alerts
|

Serum Factor V Is a Continuous Biomarker of Graft Dysfunction and a Predictor of Graft Loss After Liver Transplantation

Abstract: Factor V is an early marker for EAD and is a continuous predictor of short-term graft loss after LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Recently, it has been demonstrated than serum factor V was shown to predict early graft loss and patient survival 42,43 . Furthermore, different experimental studies showed that serum concentrations of glycocalyx components or the release of hepatocyte‐derived microRNAs could predict 1‐year graft loss 44–47 …”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated than serum factor V was shown to predict early graft loss and patient survival 42,43 . Furthermore, different experimental studies showed that serum concentrations of glycocalyx components or the release of hepatocyte‐derived microRNAs could predict 1‐year graft loss 44–47 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, microRNAs and circular RNAs, such as miRNA-122, circFOXN2, and circNEXTIN3, that are expressed in the liver have been found to be potential early predictors of the onset of EAD ( 6 , 7 ). In addition, serum protein profiles of recipients associated with EAD have been widely studied, and several serum proteins have been identified, such as monocyte chemoattractant protein 1, interleukin 8, factor V, and soluble CD163 ( 8 , 9 , 17 ). However, protein profiles in donor grafts associated with EAD are rarely studied.…”
Section: Discussionmentioning
confidence: 99%
“…8 Acute kidney injury (AKI) was defined as a >50% rise in the post-LT serum creatinine from the baseline level. 9,10 Patient and graft survival…”
Section: Definitionsmentioning
confidence: 99%